2016
DOI: 10.1161/circulationaha.116.022967
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Hydrogen Sulfide Production in Diabetic Mice Improves Reparative Function of Bone Marrow Cells

Abstract: Background Bone marrow cell-based treatment for critical limb ischemia (CLI) in diabetic patients yielded a modest therapeutic effect due to cell dysfunction. Therefore, approaches that improve diabetic stem/progenitor cell functions may provide therapeutic benefits. Here, we tested the hypotheses that restoration of hydrogen sulfide (H2S) production in diabetic bone marrow cells (BMCs) improves their reparative capacities. Methods Mouse BMCs were isolated by density-gradient centrifugation. Unilateral hind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 57 publications
3
65
0
Order By: Relevance
“…These results are in agreement with the recent studies that demonstrate that H 2 S is able to promote migration and wound healing. The underlying mechanism involves increased levels of p-Akt, p-ERK1/2 and phosphorylated glycogen synthase kinase-3b [81][82][83]. Overall these results demonstrate that prolonged cell GSGa pre-conditioning could represent a powerful tool for selecting adult stem-cell lines that maintain an increased proliferative and migration capability and resistance to oxidative stress, suggesting a potential successful approach for future in vivo/therapeutic applications.…”
Section: Discussionmentioning
confidence: 72%
“…These results are in agreement with the recent studies that demonstrate that H 2 S is able to promote migration and wound healing. The underlying mechanism involves increased levels of p-Akt, p-ERK1/2 and phosphorylated glycogen synthase kinase-3b [81][82][83]. Overall these results demonstrate that prolonged cell GSGa pre-conditioning could represent a powerful tool for selecting adult stem-cell lines that maintain an increased proliferative and migration capability and resistance to oxidative stress, suggesting a potential successful approach for future in vivo/therapeutic applications.…”
Section: Discussionmentioning
confidence: 72%
“…We flushed the iliac and femur with Dulbecco's Modified Eagle's Medium (DMEM) containing 2% FBS. Bone marrow-derived cells were separated by Ficoll density gradient centrifugation and seeded in 6-well dishes (36). Cells were cultured in minimum essential medium alpha (MEM-a) with 30 ng/ ml murine macrophage-colony stimulating factor (M-CSF) and 20 ng/ml RANKL.…”
Section: Bone Marrow-derived Cell Isolation and Osteoclast Developmentmentioning
confidence: 99%
“…However, recent publications have revealed that H 2 S is synthesized in mammalian tissues, and freely travels through cell membranes. H 2 S acts independently of any specific transporters, and it has a number of biological effects on various systems (Meng et al, ; Cao and Bian, ; Feliers et al, ; Ianaro et al, ; Katsouda et al, ; Cheng et al, ). Nowadays, H 2 S is regarded as the third endogenous gasotransmitter followed by NO and CO (Hine et al, ).…”
Section: Introductionmentioning
confidence: 99%